Impact of Self-Efficacy, Management Skills, and Family Support on Entrepreneurial Intent Among Women Entrepreneurs in East Java, Indonesia - Kristianingsih, yuyun; sudarmiatin, sudarmiatin; Rahayu, Wening Patmi (Jurnal Bisnis dan Manajemen, 2024)
This study examined the direct and indirect effects of self-efficacy, management skills, and family support on the entrepreneurial intent of women entrepreneurs in East Java, Indonesia. Employing a quantitative approach with a sample of 145 women entrepreneurs, structural equation modeling (SEM) with partial least squares (PLS) was utilized to analyze the data. The findings revealed that all three variables had a significant positive direct effect on entrepreneurial intent. Additionally, self-efficacy acted as a mediator in the relationship between management skills, family support, and entrepreneurial intent. These results highlight the crucial role of self-efficacy in fostering entrepreneurial intentions among women entrepreneurs and suggest that interventions aimed at enhancing self-efficacy, management skills, and family support can effectively promote women's entrepreneurship